2023
DOI: 10.1093/jrsssc/qlad035
|View full text |Cite
|
Sign up to set email alerts
|

Estimating a brain network predictive of stress and genotype with supervised autoencoders

Abstract: Targeted brain stimulation has the potential to treat mental illnesses. We develop an approach to help design protocols by identifying relevant multi-region electrical dynamics. Our approach models these dynamics as a superposition of latent networks, where the latent variables predict a relevant outcome. We use supervised autoencoders (SAEs) to improve predictive performance in this context, describe the conditions where SAEs improve predictions, and provide modelling constraints to ensure biological relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…13 More recently, we developed a supervised autoencoder approach to learn the electome networks, a deep learning technique common in modern machine learning that uses information from the associated behavior to force the supervised electome to capture relevant brain dynamics, even when this electome network explains a relatively small percentage of the total electrophysiological signal. 47 We demonstrated that this technique is a promising approach to address multiple sources of misspecification. 47 While unsupervised approaches require less effort to train models, they often find the strongest neural signal or the neural features that explain the most variance, not those that may be most relevant to the topic of interest.…”
Section: Effective Model Trainingmentioning
confidence: 96%
See 1 more Smart Citation
“…13 More recently, we developed a supervised autoencoder approach to learn the electome networks, a deep learning technique common in modern machine learning that uses information from the associated behavior to force the supervised electome to capture relevant brain dynamics, even when this electome network explains a relatively small percentage of the total electrophysiological signal. 47 We demonstrated that this technique is a promising approach to address multiple sources of misspecification. 47 While unsupervised approaches require less effort to train models, they often find the strongest neural signal or the neural features that explain the most variance, not those that may be most relevant to the topic of interest.…”
Section: Effective Model Trainingmentioning
confidence: 96%
“… 47 We demonstrated that this technique is a promising approach to address multiple sources of misspecification. 47 While unsupervised approaches require less effort to train models, they often find the strongest neural signal or the neural features that explain the most variance, not those that may be most relevant to the topic of interest.…”
Section: Effective Model Trainingmentioning
confidence: 96%